2016
DOI: 10.1248/cpb.c16-00135
|View full text |Cite
|
Sign up to set email alerts
|

Control of Drug Diffusion Behavior of Xanthan and Locust Bean Gum Gel by Agar Gel

Abstract: Oral gel formulations are known as easy to administer drug products for patients who have problems taking drugs including those with conditions such as dysphagia. In addition, there are numerous commercially available oral gel products, most of which are immediate-release formulation that release their pharmaceutical ingredient content by diffusion. This study is focused on developing oral gel formulations that reduce the dosing frequency and dosage compared to the conventional types. This is with the aim of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Locust bean gum (LBG), a galactomannan from the seeds of the carob tree, and salep polysaccharide, a glucomannan from the roots and tubers of orchids, have been shown to reduce strength and elongation of agar film [ 21 ]. In another study [ 22 ], the addition of a combination of LBG and xanthan gum reduced the breaking stress of the agar gel membrane. However, other studies have reported that LBG may increase the strength of agar gels [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Locust bean gum (LBG), a galactomannan from the seeds of the carob tree, and salep polysaccharide, a glucomannan from the roots and tubers of orchids, have been shown to reduce strength and elongation of agar film [ 21 ]. In another study [ 22 ], the addition of a combination of LBG and xanthan gum reduced the breaking stress of the agar gel membrane. However, other studies have reported that LBG may increase the strength of agar gels [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we assumed that incorporating FP into the agar gel would make it possible to obtain a mixed food gel with antioxidant activity. It has previously been shown that incorporating other hydrocolloids into agar gel changes its physicochemical properties [ 21 , 22 , 23 ]. Rozek et al [ 24 ] supplemented model agar gel with grape PCs.…”
Section: Introductionmentioning
confidence: 99%
“… 30 In addition, there are many oral gel products that are available commercially, most of which are quick-release formulations that release the active ingredient by diffusion. 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, there are many oral gel products that are available commercially, most of which are quick-release formulations that release the active ingredient by diffusion. 31 In this study, HPMC was used for making the GEGPA preparations, which act as a gelling agent. HPMC will form a colloidal system when dissolved in water.…”
Section: Discussionmentioning
confidence: 99%
“…When the mixing ratio of LBG was 50% or more, the hardness decreased with increase of LBG ratio. Watanabe et al described that the mixing ratio of XG and LBG which exert the maximum synergistic effect was 1:1 (Watanabe et al, 1992).Varying ratios of LBG have been shown to influence gel structure, in that gel strength suddenly decreased at certain ratios (Watanabe et al, 1992;Watanabe et al, 1993;Watanabe et al, 1996;Copetti et al, 1997;Hishikawa et al, 2016). It is believed that the structure of the straight chain of LBG and the non-straight chain of XG associate at a ratio of 1:1 (Copetti et al, 1997).In the case of this study, AG has been added to the mixture of XG and LBG (Table 1), the reason for not showing the highest hardness at XG:LBG=1:1 is considered to be due to the fact that the coexistence of AG might impair the synergistic effect.The patients felt ill with MD have to take 20-30mL each time.…”
Section: Evaluation Of Gel Propertiesmentioning
confidence: 99%